Characterization techniques: Life of Spyridon by Theodore of Paphos and its metaphrasis (Circe de clásicos y modernos, 2020)
This study analyzes the characterization techniques employed by Theodore of Paphos (7th century), as compared with those in the re-elaborated version by the anonymous 11th century author, in order to establish similarities, differences and particular intentions. The same basic strategies are used by both authors, but the metaphrast modifies them to underscore different qualities and to fit them to a different time period.
Keywords: Byzantium; hagiography; Theodore of Paphos; Spyridon; metaphrasis